The market for scientific lemons, and the marketization of science - Zamora Bonilla, Jesús (THEORIA. An International Journal for Theory, History and Foundations of Science, 2019)
Scientific research is based on the division of cognitive labour: every scientist has to trust that other colleagues have checked whether the items that are taken as knowledge, and she cannot check by herself, are reliable enough. I apply ideas from the field known as 'information economics' (the study of economic interactions where some agents are better informed than others) to analyse the scientists' incentives to produce items of knowledge of an 'adequate' quality, under the assumption that a big part of what one observes in her empirical research is not available for the readers of the paper. I also discuss some criticisms to this 'marketization' of science studies.